The Role of Public Relations in Improving Services at the Arifin Achmad Regional General Hospital (Rsud) Riau Province.: Peran Hubungan Masyarakat Dalam Meningkatkan Pelayanan Di Rumah Sakit Umum Daerah (Rsud) Arifin Achmad Provinsi Riau. - Candra, Leon; Noveana Putri, Anisa; Devis, Yesica; Amalia, Risa; Widodo, M.Dedi (Jurnal Olahraga dan Kesehatan (ORKES), 2024)
Public Relations plays a role in explaining or defending the public's unfavorable views of the institution, by presenting various data, facts and actual information. Based on the results of the initial public relations survey at Arifin Achmad Hospital, they are still experiencing problems in carrying out their role as public relations. The basis of this research is to find out the role of Public Relations in improving services at the General Hospital Arifin Achmad Riau Province in 2023. This type of research is a qualitative descriptive research. The research was carried out in July-August 2023 at Arifin Achmad Hospital in Riau Province. The writing subjects consisted of the Sub-Coordinator of law and Public Relations, the Head of General Affairs and Public Relations staff. The results showed that there were 4 roles carried out by public relations at the General Hospital Arifin Achmad Riau Province , namely the role as (1) communicator, the role of public relations as a communication liaison, namely conducting cooperative relations with other regional hospitals, conveying hospital information through communication media and not conduct two way communication with patients or the public.(2) relationship, the role of public relations as a relationship builder is not to build relationship with the media and do not receive training for internal public relations. (3) back up management, the role of public relations as a management support, namely public relations carrying out planning activities to implementation to be taken into consideration by general hospital Arifin Achmad Riau Province. (4) good image maker, the role of public relations as a positive image builder, namely by providing information in the hospital environment in the form of leaflets, banners and also outreach. In conclusion, the General Hospital Arifin Achmad Riau Province should pay attention to questions that are oriented towards hospital public relations in order to support service improvement.